1990
DOI: 10.1111/j.1439-037x.1990.tb00795.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pulp and Paper Mill Effluent Irrigation on Carbon‐di‐oxide Evolution in Soils

Abstract: Pulp and paper mill waste water irrigation increased pH, EC, organic carbon and exchangeable sodium content of soils. The increase in organic matter content of soils accelerated microbial activity and hence accelerated substrate decomposition with the release of COi. There exhibited a peak followed by a steady decline in the rate of COi evolution in effluent irrigated soils. The irrigation of pulp and paper mill combined effluent to soils did not affect microbial activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

1990
1990
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…The addition of black liquor (pH 10) resulted in rapid increases in soil pH by 0.1 to 0.5 units within 2 d and then stabilized throughout the remaining 58 d of incubation (data not shown). This result is in agreement with other studies that found an increased soil pH with alkaline paper mill effluent irrigation for 15 yr (Kannan and Oblisami, 1990a), or soils amended with alkaline mill sludge for 1 yr (Beyer et al, 1997). Increases in soil pH by black liquor indicate that black liquor has potential as a fluid liming material.…”
Section: Resultssupporting
confidence: 92%
“…The addition of black liquor (pH 10) resulted in rapid increases in soil pH by 0.1 to 0.5 units within 2 d and then stabilized throughout the remaining 58 d of incubation (data not shown). This result is in agreement with other studies that found an increased soil pH with alkaline paper mill effluent irrigation for 15 yr (Kannan and Oblisami, 1990a), or soils amended with alkaline mill sludge for 1 yr (Beyer et al, 1997). Increases in soil pH by black liquor indicate that black liquor has potential as a fluid liming material.…”
Section: Resultssupporting
confidence: 92%
“…This indicated that 524 toxicity has been reduced significantly after bacterial degra-525 dation. The growth promoting effects of untreated effluent on 526 amylase at lower concentration might be due to the presence 527 of optimum level of organic nutrients essential for plant growth 528 (Kannan and Oblisami, 1990). The reduction in amylase activity 529 at higher concentration of undegraded effluent might be due to 530 the high pollution content affecting various physiological and 531 biochemical processes during the seed germination.…”
mentioning
confidence: 98%
“…The lowering of the observed pH can be explained by a direct effect of the biolignin acidity on the soil since it is extracted by an acidic process, that is to say, formic acid and acetic acid as confirmed by Kannan and Oblisami [10] and Veeresh et al [56].…”
Section: Discussionmentioning
confidence: 75%
“…However, the application of large quantities of boiler ash also adds significant amounts of trace metals and other elements that may be harmful to plants and the environment in general. Nevertheless, the application of black liquor, as studied by Kannan and Oblisami [10,11] and Xiao et al [12], revealed an increase in organic carbon content with an improvement in the enzymatic activities in the soil.…”
Section: Introductionmentioning
confidence: 99%